Impact of Postoperative Radiotherapy on Survival of Patients With de novo Stage IV Breast Cancer: A Population-Based Study From the SEER Database - Zhang, Jie; Luo, Shiping; Qiu, Zhaozhen; Lin, Yuxiang; Song, Chuangui (Frontiers in Oncology, 2021)
Purpose.In our study, we aimed to evaluate the role ofpostoperative radiotherapy for patents with de novo stage IV breast cancer. Patients and Methods. Patients diagnosed with stage IV breast cancer from 2010 to 2016 were selected from the Surveillance, Epidemiology, and End Result (SEER) database. Those patients who received both chemotherapy and surgery and lived longer than 6 months were divided into radiotherapy and non-radiotherapy groups. Kaplan-Meier analysis and multivariate Cox proportional hazards models were used to estimate the survival outcomes before and after being1:1 propensity score matched (PSM). Subgroup analyses stratified by age, subtype, status of distant metastasis, and surgery type were also performed. Results.Among 1935 patients, 52% (1006) underwent radiotherapy while the non-radiotherapy group contained 48% (929).After PSM, a total of 1520 patients in two groups of 760 patients were enrolled in this analysis. Kaplan-Meier and the multivariate survival analysis demonstrated that the radiotherapy group presented with a better prognosis compared to the non-radiotherapy group(after PSM, BCSS: Hazard Ratio, 0.697; 95% confidence interval, 0.59-0.823; P<0.001; OS: Hazard Ratio, 0.707; 95% confidence interval, 0.601-0.831; P<0.001). Further subgroup analyses showed the Luminal subtype (HR+/HER2-), triple-negative breast cancer (TNBC), and bone-only metastasis patients presented with the most promising survival in the radiotherapy group. Conclusions.Postoperative radiotherapy is associated with a significant survival advantages in BCSS and OS.It can be an optimal supplementary treatment for stage IV patients after surgery, especially for Luminal subtype, TNBC, and patients with a low metastatic burden.